A Concept of a Platform for Data-Driven Approach to Detect Cognitive Biases with Feedback - Fafuła, Aleksander (Projekt platformy do wykrywania błędów poznawczych poprzez podejście zorientowane na dane ze wsparciem, 2010)
Cognitive biases often influence decision processes related to investment on stock markets. Mainly, these concern complex problems with perception and understanding of surrounding reality. This research was aimed to detect cognitive biases in the data-driven manner. A few basic cognitive biases are examined: gambler’s fallacy, base rate fallacy, clustering illusion, bandwagon effect, overconfidence effect. This paper presents a new concept of a platform which can detect specific users behaviours. Finally users evaluate algorithms and rules found. Along with the standard functionalities of a stock market simulator a few methods of data mining will be applied: inductive decision trees, associations, clustering and more.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 118-128
Keywords: cognitive biases; trading simulator; trading support software; patterns in behaviour